Speciation of Sedimentary Phosphorus in an Urban Wetland: The Case of El Oulfa Pound. Casablanca, Morocco - Nachchach Badr; Jounaid Halima; Taoufik Mohammed; Chakri Nihad; Elamrani Btissam; Dialo Wandé (E3S Web of Conferences, 2024)
Eutrophication remains a major concern for the quality of surface waters worldwide. This phenomenon significantly restricts water usage. The El Oulfa pond, located in Casablanca, is experiencing advanced eutrophication primarily caused by domestic wastewater discharge. Despite the cessation of these discharges and the implementation of an aeration system coupled with biological treatment, physicochemical analyses of the water body have shown an increase in phosphorus levels. This situation suggests a sedimentary origin for this nutrient, considered a limiting factor in eutrophication. This study aims to determine the various fractions of sedimentary phosphorus and their involvement in the eutrophication of the pond, using sequential chemical extraction according to Golterman. This sequential extraction revealed that the bioavailable phosphorus bound to organic matter (ASOP) represents 60.45% of the total phosphorus. Regarding mineral phosphorus, the fraction bound to calcium (CaCO3-P) is the most dominant, while the bioavailable fraction bound to iron (P-Fe) accounts for only 1.63% of the total phosphorus.